Fishermen's Livelihood Adaptation in Response to Climate Change: An Empirical Study on South-Western Coastal Zone of Bangladesh - Rayhan, SM; Mou, Anika Tahsin; Akter, Bably; Kabir, Md Shajahan; Hoque, Md Najmol (Research in Agriculture Livestock and Fisheries, 2023)
This study aimed to understand the livelihood status of the fishery-dependent communities in the South- Western coast of Bangladesh and their livelihood adaptation in response to climate change. The study was carried out in two villages of Dacope upazila in Khulna District. Data were collected from a purposively drawn sample of 60 fisher’s households through household interviews, key informants’ interviews, and transect walk as well as from secondary sources. The adverse climatic variability influences all the livelihood capitals and strategies of fishing communities. Most households have lower access to sanitation, market transportation, health facilities, GO, and NGO services during the adverse climatic situation. Increased levels of cyclones and floods result in greater damage to fishing equipment, livelihood assets, and lower level of fish catch. Income generation from fisheries-related activities is reducing gradually which affects the livelihoods of the fishers. The study has identified four different practices of adaptation to climate change by those fishing communities where about 71.67% adopted livelihood diversification. To cope with the changing climate and variability most of the fishing households (95%) have taken multiple adaptation strategies while the rest (5%) did not. The fishermen are exploited financially by the local credit facility provider. Diversification of livelihoods included agriculture (23.26%), fish trading (2.33%), fish farming (18.60%), and other different types of diversification found in the study area due to climate impacts but not always sufficiently fruitful. This situation may worsen over the next few decades and an improved level of responsiveness would be required. Vol. 9, No. 3, December 2022: 337-351